2004
DOI: 10.1111/j.1538-7836.2004.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalating safety study of a new oral direct thrombin inhibitor, dabigatran etexilate, in patients undergoing total hip replacement: BISTRO I

Abstract: USATo cite this article: Eriksson BI, Dahl OE, Ahnfelt L, Kä lebo P, Stangier J, Nehmiz G, Hermansson K, Kohlbrenner V. Dose escalating safety study of a new oral direct thrombin inhibitor, dabigatran etexilate, in patients undergoing total hip replacement: BISTRO I. (12.5, 25, 50, 100, 150, 200 and 300 mg twice daily or 150 and 300 mg once daily) administered 4-8 h after surgery, for 6-10 days. Dose escalation was based on clinical and pharmacokinetic data. The primary safety outcome was major bleeding. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
162
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(173 citation statements)
references
References 11 publications
6
162
0
5
Order By: Relevance
“…46 This study could prove dabigatran to be superior at doses of 150 and 225 mg bid. 47 Subsequently, three larger Phase III studies for the treatment of deep venous thrombosis compared dabigatran (150 mg or 220 mg once daily) with enoxaparin.…”
Section: Clinical Trials Of Dabigatranmentioning
confidence: 94%
“…46 This study could prove dabigatran to be superior at doses of 150 and 225 mg bid. 47 Subsequently, three larger Phase III studies for the treatment of deep venous thrombosis compared dabigatran (150 mg or 220 mg once daily) with enoxaparin.…”
Section: Clinical Trials Of Dabigatranmentioning
confidence: 94%
“…Dabaigatran etexilate is a pro-drug of the direct thrombin inhibitor, dabigatran (Eriksson et al, 2004). There have been four phase III clinical trials comparing this drug to enoxaparin.…”
Section: Current Oral Anticoagulantsmentioning
confidence: 99%
“…The efficacy and safety of dabigatran for prevention of VTE in elective major orthopaedic surgeries was first demonstrated in the Boehringer Ingelheim Study in ThROmbosis (BISTRO) phase II trials [44,51,52]. The principle results from this set of studies showed that increasing doses of dabigatran etexilate decreased total VTE in a dosedependent manner, and the incidence of major VTE (proximal DVT and/or PE) was lower in groups with any dose of dabigatran etexilate (1.7%-5.0%) compared with enoxaparin (5.6%).…”
Section: Prevention Of Venous Thromboembolism After Hip or Knee Replamentioning
confidence: 99%